DEVELOPMENT OF A FEASIBILITY STUDY FOR AN INNOVATION PROJECT - A. R. Lukmanov (Финансы: теория и практика)
The transition to the innovative type of development in particular and the innovative economy in general is expected to facilitate movement to the new tenor of technology for the Russian Federation. This, in turn, would allow the country to compete on an equal basis with other developed economies. Therefore, the issue of handling innovations is particularly important today. The paper describes a methodology for modifying the existing development standards using the UNIDO method as an example. The proposed version of a feasibility study to be submitted to potential investors makes it more accessible to inventors, and hence enhances their ability to bring their innovations to the market, which to a certain degree could give impetus to the development of the whole economic system of the country.